Astaxanthin prevents pulmonary fibrosis by promoting myofibroblast apoptosis dependent on Drp1‐mediated mitochondrial fission. Issue 9 (27th June 2015) - Zhang, Jinjin; Xu, Pan; Wang, Youlei; Wang, Meirong; Li, Hongbo; Lin, Shengcui; Mao, Cuiping; Wang, Bingsi; Song, Xiaodong; Lv, Changjun
Abstract Promotion of myofibroblast apoptosis is a potential therapeutic strategy for pulmonary fibrosis. This study investigated the antifibrotic effect of astaxanthin on the promotion of myofibroblast apoptosis based on dynamin‐related protein‐1 (Drp1)‐mediated mitochondrial fission in vivo and in vitro. Results showed that astaxanthin can inhibit lung parenchymal distortion and collagen deposition, as well as promote myofibroblast apoptosis. Astaxanthin demonstrated pro‐apoptotic function in myofibroblasts by contributing to mitochondrial fission, thereby leading to apoptosis by increasing the Drp1 expression and enhancing Drp1 translocation into the mitochondria. Two specific siRNAs were used to demonstrate that Drp1 is necessary to promote astaxanthin‐induced mitochondrial fission and apoptosis in myofibroblasts. Drp1‐associated genes, such as Bcl‐2‐associated X protein, cytochrome c, tumour suppressor gene p53 and p53‐up‐regulated modulator of apoptosis, were highly up‐regulated in the astaxanthin group compared with those in the sham group. This study revealed that astaxanthin can prevent pulmonary fibrosis by promoting myofibroblast apoptosis through a Drp1‐dependent molecular pathway. Furthermore, astaxanthin provides a potential therapeutic value in pulmonary fibrosis treatment.